Evaluation of PE Films Having NIR-Reflective Additives for Greenhouse Applications in Arid Regions - Syed K. H. Gulrez; Ahmed M. Abdel-Ghany; Ibrahim M. Al-Helal; Saeed M. Al-Zaharani; Abdullah A. Alsadon (Advances in Materials Science and Engineering)
Linear-low-density-polyethylene- (LLDPE-) based formulations with several near-infrared- (NIR-) reflective pigments were prepared by melt blending technique and their subsequent films were prepared by blown film extrusion process. Thermal properties of these films were evaluated using differential scanning calorimetry (DSC). The results showed that the melting and crystallization temperatures (Tm and Tc, resp.) of these formulations were almost similar to that of control resin. The melt viscosity was measured by stress-controlled rotational rheometer and melt flow index (MFI) instruments. Rheological measurements indicated that the blend formulations with NIR-reflective additive have similar melt viscoelastic behavior (storage modulus and dynamic viscosity) to the control resin. The mechanical test performed on NIR-reflective films showed similar values of tensile strength for blend samples as that of control resin. The spectral radiometric properties of the blend films were evaluated in the solar wavelength range of 200–1100 nm and found to be improved over the control sample without having NIR-reflective pigment.